Celebrity in death - Robb, J. D., 1950- (New York : G.P. Putnam's Sons, 2012)
NYC Lt. Eve Dallas investigates the death of a young actress with the assistance of her husband Rourke and Detective Peabody.
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Mystery fiction